2012
DOI: 10.1108/09600031211258138
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain practices and company performance: the case of 3PLs in Italy

Abstract: Purpose – The pressure on logistics companies to embrace green processes has increased significantly in the last few years. Within the broad concept of green supply chain management, a review of the existing literature has highlighted a need to understand how green supply chain practices (GSCP) can contribute to improving company performance from an environmental point of view, as well as economic and operational. This paper aims to investigate the GSCP adopted by third party logistics (3PLs) in Italy in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
212
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(241 citation statements)
references
References 84 publications
(151 reference statements)
6
212
1
3
Order By: Relevance
“…Therefore, CSR is likely to gain in importance as a way to enhance economic performance in the industry. Existing studies confirm that LSPs perceive for example green supply chain performance as being linked to a positive overall result (Perotti et al, 2012). Sustainability, particularly environmental sustainability of LSPs is also expected to become more important as a supplier selection criterion (Wolf and Seuring, 2010).…”
Section: Lsps and Their Role In The Sustainability Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CSR is likely to gain in importance as a way to enhance economic performance in the industry. Existing studies confirm that LSPs perceive for example green supply chain performance as being linked to a positive overall result (Perotti et al, 2012). Sustainability, particularly environmental sustainability of LSPs is also expected to become more important as a supplier selection criterion (Wolf and Seuring, 2010).…”
Section: Lsps and Their Role In The Sustainability Agendamentioning
confidence: 99%
“…This resulted in a new, emerging role of LSPs as orchestrators of supply chains, serving a leadership function to help facilitate improvements and best practices across all nodes (Zacharia et al, 2011). The critical positioning of LSPs to support the efforts to improve the sustainability of supply chain operations is acknowledged in the literature (Perotti et al, 2012). Sustainable service offering can be viewed as a form of innovation or differentiation, i.e.…”
Section: Lsps and Their Role In The Sustainability Agendamentioning
confidence: 99%
“…Impact of green actions on 3PLs' performance [3,38,40,41,56,61,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Content Analysismentioning
confidence: 99%
“…The results showed that, despite the global recession, many large 3PLs increased their commitments to building environmental sustainability programs that include transportation-related actions, administrative and analytical initiatives. Perotti et al (2012) [61] conducted a study on 15 3PLs operating in Italy. The results revealed that the adoption of green supply chain actions was substantially low, whereas the most implemented green actions referred to vehicle energy efficiency and recycling materials.…”
Section: Green Actions and The Impact On 3pls' Performancementioning
confidence: 99%
“…At the same time, compliance with very basic requirements is enough for logistics providers to be qualified and included into tender process. Perotti et al (2012) conducted a multiple case empirical research in order to understand how green supply chain practices may influence third party logistics company's performance. On the one hand, there is a number of green supply chain practices that have certain impact: − Green supply; − Distribution strategies and transportation; − Warehousing and green building; − Reverse logistics; − Cooperation with customers; − Investment recovery; − Eco-design and packaging; − Internal management.…”
Section: Green Logistics and Environmental Issuesmentioning
confidence: 99%